THE RHABDONELLIDAE (TINTINNINA:OLIGOTRICHIDA) FROM ATOL DAS ROCAS AND FERNANDO DE NORONHA ARCHIPELAGO, SOUTHWESTERN ATLANTIC, BRAZIL - Nogueira, Eliane Maria de Souza; Sassi, Roberto; Cordeiro, Tarcísio Alves (Arquivos de Ciências do Mar, 2017)
Plankton species of the family Rhabdonellidae (Tintinnina: Oligotrichida) were studied in this work using material collected in 28 oceanographic stations around Atol das Rocas and Fernando de Noronha Archipelago, off Northeast Brazil. A total of seven species belonging to three genera were identified: Protorhabdonella, with two species: P. curta and P. simplex; Rhabdonella, with four species: R. amor, R. cornucopia, R. elegans, R. henseni and R. hydria; and Rhabdonellopsis with only one species: R. apophysata. Four species (R. amor, R. apophysta, R. elegans, and P. simplex) were found in most of the samples, and R.cornucopia and R. hydria are reported here for the first time in Northeast Brazil. All species are described, drawn by using a camera lucida, and measured using a micrometric eyepiece. Details regarding its worldwide distribution are presented.